A Developmental Study of the Self‐Prioritization Effect in Children Between 6 and 10 Years of Age. Issue 3 (3rd January 2020) - Maire, Hélène; Brochard, Renaud; Zagar, Daniel
Abstract : Self‐biases are well described in adults but remain poorly understood in children. Here, we investigated in 6–10 year‐old children ( N  = 132) the self‐prioritization effect (SPE), a self‐bias which reflects, in adults, the perceptual advantage for stimuli arbitrarily associated with the self as compared to those associated with other persons. We designed a child‐friendly adaptation of a paradigm originally introduced in adults by Sui, He, and Humphreys (2012) in order to test whether the SPE also occurs in children and if so, to determine its evolution with age. A robust SPE was obtained from the age of 6, and this effect was similar‐sized in our four age groups. These findings are discussed with reference to the development of the self during childhood.